Preparation, Characterization, and in - vivo Evaluation of Daptomycin Poly(D,L-lactide-co-glycolide) Microspheres - H. Samein, Laith (Iraqi Journal of Pharmaceutical Sciences, 2017)
Polymeric microsphere devices occupy a wide range in the field of controlled drug delivery. Subcutaneous injectable preparations of Poly(Lactide-co-Glycolide) (PLGA) microsphere of Daptomycine were prepared by solvent extraction/evaporation technique using different copolymers ratio and molecular weights. Four formulations were prepared (F1-F4) and characterized in term of particle size, surface morphology, bulk density and porosity in addition to the drug content. The effects of the above parameters on the in-vitro release study were evaluated. These formulas were evaluated also for their in-vivo release profile using rat (as an animal model) and their serum daptomycin concentration were evaluated accordingly. A trapezoidal method was used to estimate the cumulative AUC parameter and the effect of copolymers ratio and molecular weights on the shape of AUC for four formulas were evaluated. Simulation study was performed (for 7 or 10 days dosing of F1 and F2 and 15 day dosing for F3 and F4) as a predictor of the steady state concentration and other pharmacokinetics parameters. It was inferred from this study that by using tailored formulation approach, long and short acting preparations of injectable daptomycin microsphere could be developed helping to provide the clinicians more flexibility to select the suitable preparation according to the patient need.Key words: Daptomycin, trapezoidal,microsphers ,simulation .